Results on elastic cross sections in proton-proton collisions at √s = 510 GeV with the STAR detector at RHIC - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physics letters, 2024)
We report results on an elastic cross section measurement in proton-proton collisions at a center-of-mass energy √s=510 GeV, obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section is measured in the four-momentum transfer squared range 0.23≤−t≤0.67 GeV2. This is the only measurement of the proton-proton elastic cross section in this t range for collision energies above the Intersecting Storage Rings (ISR) and below the Large Hadron Collider (LHC) colliders. We find that a constant slope B does not fit the data in the aforementioned t range, and we obtain a much better fit using a second-order polynomial for B(t). This is the first measurement below the LHC energies for which the non-constant behavior B(t) is observed. The t dependence of B is also determined using six subintervals of t in the STAR measured t range, and is in good agreement with the phenomenological models. The measured elastic differential cross section dσ/dt agrees well with the results obtained at s=540 GeV for proton-antiproton collisions by the UA4 experiment. We also determine that the integrated elastic cross section within the STAR t-range is σelfid=462.1±0.9(stat.)±1.1(syst.)±11.6(scale) μb.
The STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen [und viele weitere]
Online verfügbar 5 April 2024, Version des Artikels 12 April 2024
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Gesehen am 14.05.2025